Incidence and demographic risk factors for leptospirosis in dogs in the UK. (31st May 2021) - Taylor, Collette; O'Neill, Dan G.; Catchpole, Brian; Brodbelt, Dave C.
Abstract: Objectives: To estimate the annual incidence risk of leptospirosis diagnosis in practice‐attending dogs in the UK during 2016 and identify risk factors for diagnosis. Methods: Incidence of leptospirosis diagnosis in dogs during 2016 was estimated from dogs in primary‐care practices from the VetCompass Programme ( n  = 905, 543). A case‐control study of laboratory cases ( n  = 362) versus VetCompass controls explored factors (age, sex, neutering, breed, Kennel Club group, urban‐rural location, indices of deprivation) associated with leptospirosis diagnosis through multivariable logistic regression. Results: Annual incidence risk of leptospirosis in the VetCompass population was 0.8 cases per 100, 000 dogs (0.0008%, 95% CI 9.1 × 10 –8 –5.2 × 10 –5 ). Adult dogs, especially 1‐ < 5 years olds (odds ratio [OR] = 0.38, 95% CI 0.27–0.54), and dogs attending urban clinics (OR = 0.26, 95% CI 0.19–0.35) had reduced odds of leptospirosis versus dogs < 1 year old and rural dogs, respectively. Dogs attending clinics in less deprived areas had increased odds of diagnosis (OR = 3.63, 95% CI 2.28–5.78) compared to crossbreds, Cocker Spaniels (OR = 4.25, 95% CI 2.65–6.84), Collies (OR = 3.53, 95% CI 2.22–5.62) and Lurchers (OR = 3.49, 95% CI 1.50–8.11) had increased odds of diagnosis. Discussion: Leptospirosis is rarely diagnosed in clinical practice, suggesting that many true cases may be missed. Demographic risk factors identified here may inform the index of suspicion and encourage increased use of confirmatory diagnostic testing.